Damnatio mermoriae or creatio memoriae? Memory sanctions as creative processes in the fourth century AD - Omissi, A (Cambridge University Press, 2016)
Damnatio memoriae, the ill-defined group of processes that we often now refer to by the term ‘memory sanctions’, is generally thought of in wholly negative terms. It is imagined as a process of destruction, of erasure, and of silence. Yet these complex assaults on the memory of fallen enemies were far more than simply destructive processes. Through the example of Magnus Maximus (383–8) and his commemoration in Rome and Constantinople during the reign of Theodosius I, this article considers how memory sanctions could be generative of historical material and how emperors used oratory, ceremony and triumphal architecture to memorialise their fallen enemies.